Immunotactoid Glomerulopathy with Nontuberculous Mycobacterial Infection: A Novel Association - Yoshio Shimizu (Case Reports in Nephrology and Dialysis, 2021)
A 70-year-old woman underwent a renal biopsy due to nephrotic syndrome. She had suffered from nontuberculous mycobacterial infection (NTM) for 14 years. The patient was diagnosed as having membranoproliferative glomerulonephritis (MPGN) type 3 and immunoglobulin (Ig)-associated MPGN based upon LM/erythromycin and IF findings, respectively. In high-magnification imaging, electron-dense deposits showed immunotactoid glomerulopathy (ITG). There was no evidence of hematological cancer, and the patient improved after receiving treatments for NTM. To the best of our knowledge, this patient is the first to show an association between ITG and NTM. Although ITG is generally considered as related to lymphoproliferative disease, it is suggested that ITG is driven by bacterial infection and is a potential outcome of Ig-associated MPGN.